Impact of Electricity Shortage on Daily Routines: A Case Study of Pakistan. Issue 5 (September 2013) - Lodhi, Rab Nawaz; Malik, R. K.
People in Pakistan are facing many problems due to load shedding which is a result of electricity shortages. This study investigated the consequences of electricity shortage on daily routines and overall performance of people in Pakistan. Data has been collected through video recorded interviews and written comment-based interviews using a social network of "Face Book" as suggested by QSR-International (2012). Sample includes students, housewives, professional workers and businessmen who are living in Pakistan. The study identified 22 different results of electricity shortage in daily routines of people in Pakistan. Sleeplessness, incompletion of tasks, use of alternative resources and inefficient learning have been found to be the more critical results of electricity shortage. Furthermore, these consequences of electricity shortage can be divided into social and psychological problems. It is concluded that the shortage of electricity has changed the lives of people in Pakistan irrespective of their professions.